Mathematical Literacy Ability in Learning Problem-Based Learning with Ethnomatic Mathematics Based on Student Learning Styles - Imam, Fathul; Zaenuri, Zaenuri; Eko Nugroho, Sunyoto (Universitas Negeri Semarang, 2020)
The purpose of this study is to determine the effectiveness of the problem-based learning model with nuances of ethnomatatics on the ability of mathematical literacy and determine patterns of mathematical literacy ability in terms of the students’ leaning styles. The study was conducted at SMA Negeri 1 Mranggen. The research method used is a combination research method with a concurrent embedded model. The sampling technique uses cluster random sampling. Data collection uses documentation, questionnaires, test results, and interviews. The results showed (1) the model of problem-based learning nuanced effective ethnomatematics against students' mathematical literacy abilities; (2) The mathematical literacy ability of students with visual learning styles can choose and apply simple problem-solving strategies, students with audio learning styles can work effectively with concrete but complex models and situations, and students kinesthetic learning styles can conceptualize and generalize using information based on complex problems and situations.